English Idiomatic Expressions in EFL Classroom through Movies: Challenges and Opportunities - Saraswati, Nais (Universitas Indo Global Mandiri, 2024)
This paper investigates the use of movies in teaching idiomatic expressions within English Language Teaching (ELT), focusing on both challenges and opportunities. Using a library-based research methodology, the study synthesizes findings from existing literature to address key questions about the primary challenges, benefits, and best practices associated with this teaching approach. The analysis identifies cultural barriers, contextual complexity, and student engagement as significant challenges. Conversely, movies enhance comprehension and retention, provide cultural enrichment, improve listening and speaking skills, and encourage autonomous learning. The findings suggest that movies, when carefully selected and appropriately used, can be a powerful tool in ELT, offering a dynamic and effective method for teaching idiomatic expressions. This study provides practical recommendations for educators on integrating movies into their teaching strategies to maximize educational outcomes. Keywords: English idiomatic expressions, ELT classrooms, challenges and opportunities, movies in education